The Important Role of Interleukin-2 in COVID-19 - Leila Ghanbari Naeini; Laleh Abbasi; Farzaneh Karimi; Pajman Kokabian; Fahimeh Abdi Abyaneh; Delaram Naderi (Journal of Immunology Research)
There is controversial literature about the effects of the interleukin-2 (IL-2) cytokine family in COVID-19 pathogenesis and immunity. So we aimed to identify the potential in the role of the IL-2 family in COVID-19. A narrative review search was done through online databases, including PubMed, Scopus, and Web of Science. The search deadline was up to December 2022. We applied no time limits for the searching strategy. After retrieving articles from the databases, the authors summarized the data into two data extraction tables. The first data extraction table described the changes in the IL-2 cytokine family in COVID-19 and the second table described the therapeutic interventions targeting IL-2 family cytokines. The results of the literature on the role of the IL-2 cytokine family do not show a singular rule. IL-2 cytokine family can change during severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. Some studies suggest that IL-2 cytokine family rise during the infection and cause severe inflammatory response and cytokine storm. These cytokines are shown to be increased in immunocompromised patients and worsen their prognosis. In individuals without underlying disease, the upregulation of the IL-2 family shows the clinical outcome of the disease and rises with disease severity. However, some other studies show that these cytokines do not significantly change. IL-2 cytokine family is mostly upregulated in healthy individuals who had vaccination, but immunocompromised patients did not show significant changes after a single dose of vaccines, which shows that these patients need booster doses for efficient immunity. IL-2 cytokine family can also be used as immunotherapy agents in COVID-19.